What effect do substorms have on the content of the radiation belts?. Issue 7 (9th July 2016) - Forsyth, C.; Rae, I. J.; Murphy, K. R.; Freeman, M. P.; Huang, C.‐L.; Spence, H. E.; Boyd, A. J.; Coxon, J. C.; Jackman, C. M.; Kalmoni, N. M. E.; Watt, C. E. J.
Abstract: Substorms are fundamental and dynamic processes in the magnetosphere, converting captured solar wind magnetic energy into plasma energy. These substorms have been suggested to be a key driver of energetic electron enhancements in the outer radiation belts. Substorms inject a keV "seed" population into the inner magnetosphere which is subsequently energized through wave‐particle interactions up to relativistic energies; however, the extent to which substorms enhance the radiation belts, either directly or indirectly, has never before been quantified. In this study, we examine increases and decreases in the total radiation belt electron content (TRBEC) following substorms and geomagnetically quiet intervals. Our results show that the radiation belts are inherently lossy, shown by a negative median change in TRBEC at all intervals following substorms and quiet intervals. However, there are up to 3 times as many increases in TRBEC following substorm intervals. There is a lag of 1–3 days between the substorm or quiet intervals and their greatest effect on radiation belt content, shown in the difference between the occurrence of increases and losses in TRBEC following substorms and quiet intervals, the mean change in TRBEC following substorms or quiet intervals, and the cross correlation between SuperMAG AL (SML) and TRBEC. However, there is a statistically significant effect on the occurrence of increases and decreases in TRBEC up to a lag of 6 days. Increases in radiation belt content show a significant correlation with SML and SYM‐H, but decreases in the radiation belt show no apparent link with magnetospheric activity levels. Key Points: The radiation belts are inherently lossy Substorms increase the likelihood of an increase in the radiation belts to 50% The radiation belts have a memory of magnetospheric activity for up to 6 days